KLASIFIKASI ‘IDDAH PERSPEKTIF AL-QUR’AN: (Studi Kitab Tafsir Lubab al-Ta’wil Fi Ma’ani Tanzil Karya al-Khazin) - latansa, andressa muthi' (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Abstract The main issue discussed in this article is al-Khazin's view of the classification of iddah. This article is library research, descriptive analytical in nature. In analyzing the research data, we use a deductive method by putting forward theories, postulates or generalizations of a general nature, then presenting specific facts, and using descriptive methods.There are several provisions for the classification of 'iddah which are explained in al-Khazin's interpretation of the verses of 'iddah, namely: (a). 'Iddah for pregnant women is until giving birth, due to thalaq or the death of her husband. (b). The 'iddah for women whose husbands die and are not pregnant is up to four months and ten days.(c).The ‘iddah of women who have performed dukhul after being dukhul or not yet having dukhul is that there are two divisions, either those who are still experiencing menstruation, namely for three quru' or not experiencing menstruation because of the age of menopause or the child has not yet reached puberty, has not experienced menstruation, period The 'iddah is for three months, whereas if the thalaq has not been completed at all then there is no 'iddah period. (d). The 'iddah period for slave slaves is the same as for free women. Key word: classification of ‘iddah, al-Khazin, interpretation